Work Stress As Mediation of Influence Work Family Conflict on Cyberloafing Behavior of Employees - Rahayu, Afika; Zona, Mega Asri (Human Resource Management Studies, 2023)
This research analyzes the effect of work family conflict on cyberloafing behavior through work stress on employees at PT. Telkom Indonesia Witel, West Sumatra. This research is a type of quantitative research and is a causal research. The population in this study were all employees at PT. Telkom Indonesia Witel West Sumatra, with a total of 58 people. The sampling technique was taken using total sampling where the number of samples is the same as the population, namely 58 people. Collecting data using a survey with a questionnaire. The analysis technique used is PLS (Partial Least Square), which is a structural equation analysis technique (SEM) using SmartPLS 4 software. The results of data processing in this study indicate that work stress mediates the influence between work family conflict and cyberloafing behavior among employees at PT. Telkom Indonesia Witel West Sumatra.